Oracles, pilgrims and calendars in Pachacamac sanctuary - Pinasco Carella, Alfio (2018)
The Sanctuary of Pachacamac is a repository of memory for the ancient Andean world. However, is this memory comprehensive? How much has been forgotten, misunderstood? This essay reviews early chronicles and basic notions of Inca ontology thus proposing a revision to the possible types and hierarchies of pilgrims and oracles operating in the sanctuary, questioning the idea of one single oracle and one single kind of pilgrim. It also explains the alignment of its urban layout with respect to certain celestial bodies linked to the Inca calendar, and possible ceremonies performed in specially oriented buildings. This would support diagnosing and forecasting weather for agricultural purposes as well as water propitiation rituals.